The Roald Dahl Treasury - Dahl, Roald (Random House, Inc, 1998)
This beautiful treasury brings together some of the most dazzling moments in the work of Roald Dahl with illustrations by Quentin Blake and many other notable illustrators.
Keywords: Animal Stories